«“The Golden Age” of the Crimean Karaites»: publication of the new academic series - Grigorii Kondratjuk (Крымское историческое обозрение)
The review examines new publications on the history of Karaites – the monographs “Karaites in the Russian Empire in the late 18th – early 20th centuries” and the “Karaite communities: biographies, facts and documents (late 18th – early 20th centuries”. They studied a significant chronological period – from the time of the Karaites appearing in the Crimea and up to the beginning of the 20th century. A reasoned conclusion is made that the so-called “ The Golden Age” is the most tense in the history of the Karaite people – the time from the annexation of the Crimean Peninsula to the Russian Empire in 1783 and until 1917. It was during these 100 years when the significant transformations took place in the old-timers communities of the peninsula, when the ideas of Russian culture and education spread among the Crimean Karaites, and they themselves were actively integrated into Russian social structures. The monographs are equipped with a detailed historical excursion, which reveals many relevant and little-known facts from the past of the Karaites.